Nanotechnology in Malaysia : a new paradigm - Hamdan, Halimaton (2007)
Nanotechnology is defined as the science of material and systems with structures and components which display improved novel physical, chemical and biological properties; phenomenon that exist in the nano size scale (l-JOOnm). A nanometer (nm) is one billionth of a meter. Nanotechnology not only enables further technical and sCientific advancement of existing technologies, rather creates new technology and imposes drastic impact on industries, economy and society in the coming decades. This means that investment in nanotechnologies is imperative for a developing nation like Malaysia in order to remain competitive and ensure a future growth industry in its own right. The National Nanotechnology Initiatives of Malaysia (NNIM) was officially launched by the Deputy Prime Minister YAB Datuk Sri Najib Tun Razak on 19 September 2006. The functions, strategies and future plans of NNIM will be presented. Malaysia has spent more than RM160 million on various areas of nanotechnology related research projects. The established research areas, research path and business opportunities in various areas of nanotechnology in Malaysia is proposed